2000
DOI: 10.2460/javma.2000.216.210
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral scale system to measure heart size in radiographs of cats

Abstract: The vertebral heart-size method is easy to use, allows objective assessment of heart size, and may be helpful in determining cardiomegaly and comparing heart size in sequential radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
131
4
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 10 publications
14
131
4
8
Order By: Relevance
“…The VHS measurements (7.68±0.41v) obtained were smaller than the reference values for dogs (9.7±0.7v) (Sle- eper & Buchanan 2001) but similar to those referenced for adult cats (7.5±0.30v) (Litster & Buchanan 2000). This value was also lower than the VHS measured for the tamarin (9.42±0.44v) (Wagner & Kirberger 2005), porcupine (Black et al 2011) and bat (9.7±0.5v) (Gardner et al, 2007), but greater than that observed in ferrets (5.39±0.45 -LL projection) (Onuma et al 2009).…”
Section: Discussionmentioning
confidence: 67%
“…The VHS measurements (7.68±0.41v) obtained were smaller than the reference values for dogs (9.7±0.7v) (Sle- eper & Buchanan 2001) but similar to those referenced for adult cats (7.5±0.30v) (Litster & Buchanan 2000). This value was also lower than the VHS measured for the tamarin (9.42±0.44v) (Wagner & Kirberger 2005), porcupine (Black et al 2011) and bat (9.7±0.5v) (Gardner et al, 2007), but greater than that observed in ferrets (5.39±0.45 -LL projection) (Onuma et al 2009).…”
Section: Discussionmentioning
confidence: 67%
“…In dogs, studies of VHS in puppies, adult dogs and different breeds have been performed [2][3][4][5]9]. Less research into VHS has been performed for cats than for dogs, although studies comparing kittens and adult cats have been reported [1,6]. Except dog and cat, a similar standardize study has been reported for ferrets (mean, 5.27v) [8].…”
mentioning
confidence: 75%
“…These measurements were taken and mean values were estimated to establish normality criteria. Because it is a wild species and in order to reduce the stress of containment and also knowing that the literature reports that there is no difference in the VHS values in animals between the right and left lateral decubitus (Litster & Buchanan 2000), this experiment was carried out taking the right decubitus as the base for all the measurements.…”
Section: Measuring the Vhs (Vertebral Heart Size)mentioning
confidence: 99%
“…The VHS (Vertebral Heart Size) was measured according to the protocol established by Buchanan & Bücheler (1995), Litster & Buchanan (2000), that is the sum of the heart length and heart width at its greatest diameter and its later comparison with the vertebra bodies starting at T4 (Fig.1a). These measurements were taken and mean values were estimated to establish normality criteria.…”
Section: Measuring the Vhs (Vertebral Heart Size)mentioning
confidence: 99%
See 1 more Smart Citation